PROSES DERIVASI DAN INFLEKSI DALAM BAHASA INDONESIA PADA MEDIA SOSIAL IG: SIDRAPINFO.ID - Imran Imran; Maydal Tanna (20-87-2496)
This study aims to analyze the formation of derivation and inflection words in Indonesian. There needs to be concrete evidence to know both, such as news in newspapers, magazines and other readings. This is because the processes of derivation and inflection will be understood in reading form, not just theory. This study uses a qualitative method. Data collection techniques using reading and note techniques. As for the object of research is the process of derivation and inflection, while the subject of the research is news on social media, especially Instagram randomly. The results of the study found that the news on Instagram social media found several words that underwent a process of derivation and inflection.